Penguatan Nilai Keagamaan Anak Binaan melalui Program Kemandirian Yatim Dhuafa LKSA Rumah Yatim Kota Medan - Intan Maghdalena; Fajar Utama Ritonga; Mia Aulina Lubis (Yayasan Literasi Sains Indonesia, 2024)
The orphan and poor self-reliance program is a values and life skills-based orphan empowerment program for foster children and children assisted by Rumah Yatim by developing children's potential so that they are able to live in society. Focusing on the curriculum points of the orphan self-reliance program, including religious ability, yaumiyah, morals, academic values and skills. Morals/character are one of the main points inherent in a person, especially children, where apart from academic education, strengthening religious values themselves is really needed by children in the current environment and in the future. The purpose of this writing is as a result of the author's dedication in carrying out Field Work Practices II at Rumah Yatim Ar-Rohman Institution. The method used is qualitative research with data collection techniques through observation and interviews and using Macro Social Work Techniques, namely Participatory Rural Appraisal (PRA) with a participatory assessment approach. Then the source of additional data from this writing is a review of related literature which can support the discussion. By strengthening religious values, it has a positive impact so that the target children can recognize and understand the importance of morals for themselves. This can be seen from the willingness to learn of the children assisted by Rumah Yatim Ar-Rohman, Medan City.